Genome reanalysis to decipher resistome, virulome, and attenuated characters of attenuated Streptococcus agalactiae strain HZAUSC001. (October 2020) - Zhang, Ze; Li, Yuhui; Hu, Minqiang; Yu, Angen
Abstract: Streptococcus agalactiae is a serious pathogen causing severe anthropozoonosis in a broad range of hosts, from aquatic animals to mammals, including humans. S. agalactiae HZAUSC001 was isolated from a moribund tilapia fish exhibiting classic clinical symptoms of streptococcosis in Zhanjiang, Guangdong, China. And it was identified as the etiological factor resulting in fish disease, but was notable because it exhibited attenuated virulence. Here, the genome of S. agalactiae HZAUSC001 was re-analyzed; we assessed the resistome and virulome and deciphered the attenuated characters of HZAUSC001. The S. agalactiae HZAUSC001 genome was assembled into one chromosome with a GC-content of 35.37% and 1972 predicted open reading frames (ORFs). Phylogenetic analysis indicated that it is evolutionarily similar to piscine GBS strains GD201008-001 and ZQ0910. After re-analyzing the published genomic sequence of HZAUSC001, we identified 38 virulence factor genes and one antibiotic-resistance gene. Note that three previously noted virulence genes, bca (C protein alpha-antigen), cpbA (choline-binding protein A) and esp (enterococcal surface protein), were absent in the virulence-attenuated strain S. agalactiae HZAUSC001 but present in the highly virulent strain S. agalactiae GD201008-001. We speculate that the absence of these three virulence genes may be associated with the attenuated traits of the HZAUSC001 strain. Collectively, our study supports that HZAUSC001 may be an excellent candidate for development of an attenuated vaccine, and our results contribute to further understanding of GBS epidemiology and surveillance targets. Highlights: The whole genome of S. agalactiae HZAUSC001 has one chromosome, with a length of 2024692 bp with a G + C-content of 35.37%. The S. agalactiae HZAUSC001 genome contains 1972 ORFs and one prophage. S. agalactiae HZAUSC001 shows high evolutionarily similarity with two piscine GBS strains. 20 virulence factor genes and 1 antibiotic-associated gene was identified. The attenuated nature may result from the absence of bca, cpbA and esp virulence genes.